Method Development for Simultaneously Determining Indomethacin and Nicotinamide in New Combination in Oral Dosage Formulations and Co-Amorphous Systems Using Three UV Spectrophotometric Techniques - Nazira Sarkis; Abdulkader Sawan (International Journal of Analytical Chemistry)
This research aims to develop methods for simultaneously determining indomethacin (IND) and nicotinamide (NCT) in binary mixtures, immediate-release capsules, sustained-release capsules, and co-amorphous systems, which were designed in 2021 to improve the solubility, dissolution rate, and stability of the amorphous state of indomethacin. Moreover, this new combination may have also other possible medical benefits. Therefore, there is a need to have simple, sensitive, and precise developed methods for simultaneous quantification analysis of IND/NCT in several different ratios. Three UV-spectrophotometry techniques were deployed: zero-crossing point in the second-order derivative, dual-wavelength in the first-order derivative, and ratio subtraction coupled with spectrum subtraction. The limit of detection and the limit of quantifications (LOD and LOQ) for IND were 0.41 and 1.25, 0.55 and 1.66, and 0.53 and 1.62 μg/mL, respectively, while for NCT were 0.53 and 1.59, 0.38 and 1.14, and 0.36 and 1.08 μg/mL, respectively. All methods were linear at least in the range of 2.5–40.0 μg/mL. All proposed methods were validated according to ICH guidelines and their application on the dosage formulations was carried out. Finally, the proposed methods were compared to a reference method for each IND and NCT, and no significant statistical variance was found.